METODE PEMBELAJARAN ONLINE PAKET C - Lekat Lekat; Rufran Zulkarnaian; Suardi Jasma (UNIB Press, Universitas Bengkulu, 2020)
The purpose of this study to describe the Implementation of electronic learning in program the Package C. This study is included in a qualitative study. The subjects in this study consisted of four people, Chairman of Institute, the Principal, Tutors, and Learning. The data in this study were collected through interview, observation and documentation techniques. The data obtained were analyzed through four stages namely, data reduction, data presentation, verification and decision making. To obtain the validity of the results of the study, researchers used the technique; Source triangulation, technique triangulation and time triangulation. The results showed that First, the First, the implementation of the C package electronic learning program is carried out in order to assist the learning process. Second, teaching materials used for example print teaching materials (Books, Modules) and also use non-printed teaching materials such as audiovisual teaching materials and web-based teaching materials. Third, electronic learning methods such as classical learning methods and tutorials. Fourth, the media used are visual and audiovisual learning media. Fifth, evaluation of learning outcomes is carried out in order to assess the results of electronic learning and the activeness of learning citizens in the learning process. Sixth, the form of electronic learning model services in the form of software applications, namely the Modle application, Seventh, The use of electronic learning models is used to help tutors and become a reference for learning. Eighth, technical implementation of online learning models in the form of discussion of tutors and learning citizens. Ninth, the learning outcomes before using online learning an average of 89.3 and after implementing electronic learning has increased an average of 98.3. Tenth, inhibiting factors and supporting the implementation of online learning external inhibiting factors namely networks and external supporting factors applied facilities offer a lot of learning ease. Key words: Implementation, Electronic Learning, PKBM Songgo Langit